The Pengaruh Edukasi Gizi dengan Media Flashcard terhadap Perubahan Pengetahuan dan Frekuensi Sarapan di SD Muhammadiyah 4 Surabaya - Ni Made Ayu Rachel Rasheeta Nuka; Niken Andini; Trias Mahmudiono (Media Gizi Kesmas, 2024)
Background: Breakfast is an activity of eating and drinking that is done until 09.00 with a menu that is guided by balanced nutrition. Breakfast can increase children's intelligence and productivity at school. Nutrition education with a play method is very suitable for school children, one of which is flashcards because there are many pictures, not much writing and more attention-grabbing. Objectives: This study aims to analyze the effect of nutrition education using flashcard media on changes in knowledge and breakfast frequency at SD Muhammadiyah 4 Surabaya. Methods: This study used a quasi-experimental method with a pre-posttest group design. The sample size was obtained using the Lemeshow formula of 30 children with a dropout anticipation of 25%. Simple random sampling method for sample selection. The study was conducted by providing nutritional education using flashcard media in the treatment group and posters in the control group. Results: Wilcoxon test results indicate that there is a difference in the average level of knowledge before and after nutrition education using flashcards (p < 0,05). Moreover, the breakfast frequency of respondents increased after receiving nutrition education using flashcards. Conclusion: It can be concluded that there is a difference in the average level of knowledge and increase in breakfast frequency in the treatment group before and after nutritional education using flashcard media. To improve children's knowledge and breakfast frequency, flashcards can be used as nutrition education media.